2020
DOI: 10.1002/jsfa.10622
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an ultrasonic spray nozzle on carbohydrate and protein‐based coating materials for blueberry extract microencapsulation

Abstract: BACKGROUND An ultrasonic spray nozzle was evaluated for the production of powders and microcapsules, using blueberry extract, modified starch (HI‐CAP 100), and whey protein isolate (WPI). The effects of ultrasonic power and the concentration of coating materials on the characteristics of the resulting samples – such as viscosity, particle size, microencapsulation efficiency, color, glass transition temperature, Fourier‐transform infrared spectroscopy (FTIR), X‐ray powder diffraction (XRD), and morphology – wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…In addition, the viscosity of the emulsion also affects the particle size distribution of microcapsule particles. It was previously reported that as the viscosity of the solutions increased, the number of large particles increased, while the number of small particles decreased [ 48 ]. In general, the particle size of microcapsules is not homogeneous and is widely distributed.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the viscosity of the emulsion also affects the particle size distribution of microcapsule particles. It was previously reported that as the viscosity of the solutions increased, the number of large particles increased, while the number of small particles decreased [ 48 ]. In general, the particle size of microcapsules is not homogeneous and is widely distributed.…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasonic nozzle technology has been implemented for spray-drying processes since it helps atomize uniform droplets, protecting the bioactive compounds [46]. In this process, a thin liquid film is formed on the resonant surface by introducing the liquid into the feed capillary at the nozzle's tip [9].…”
Section: Reviewmentioning
confidence: 99%
“…Modified starch can be obtained naturally or synthesized by chemical, physical or enzymatic processes, has adequate bioavailability, low viscosity, high solubility and low cost (Balakrishnan et al, 2021), and can be used in spray drying processes (Tatar Turan and Kahyaoglu, 2021). The use of modified starch in combination with maltodextrin and gum arabic was studied by Gupta et al (2014) obtaining ferrous sulfate microcapsules with good stability and microencapsulation efficiency above 90%; however, for Ribeiro et al (2020) the limitations of modified starch are related to its undesirable taste and poor aroma protection.…”
Section: Coating or Wall Materialsmentioning
confidence: 99%